Current practice in rehabilitating old pipes for water distribution network in Malaysia - S. S., Sufian; Noor Suraya, Romali; A. R., Rahimi; Mazlan, Abu Seman (IOP Publishing Ltd., 2021)
The water distribution network (WDN) is critical in daily life because it provides treated water to consumers. However, WDN in Malaysia is facing a significant amount of water loss during the water distribution process (i.e., non-revenue water (NRW) with an average percentage of 35.6%. While one of the leading causes of NRW is old pipes, water operators are still facing barriers to rehabilitate old pipes to new pipes. Therefore, this study aims to identify the strategies to improve current practice in rehabilitating old pipes. To achieve that objective, open-ended individual interviews will be performed with sixteen individuals that have experience in managing WDN and NRW in Malaysia. This research contributes to identify the current practice/method, which has three main categories i.e. people, technology, and process in rehabilitating old pipes from industry practitioners' perspectives, which could assist researchers and industry practitioners in developing strategies to reduce NRW among water operators. The findings of this research can help to improve WDN in reducing NRW.